Pengembangan Media Pembelajaran Board Game berbasis Science-Edutaiment untuk Meningkatkan Kemampuan Regulasi Emosi Siswa Sekolah Dasar - Richa Dwi Rahmawati (Lembaga Anotero Scientific Pekanbaru, 2025)
This research is development research (R&D) using the ADDIE model. The stages passed include: analysis: student performance and needs; design: media and material design; development: validation by media experts and material experts; implementation: product trials in small groups and the final evaluation stage. Media components consist of: 1) game board; 2) toy animals; 3) preservation card; 4) dice and bucket; 5) “the treasure map” module. Product validation by media experts with a percentage result of 81.81%. validation by material experts was 80.83% and validation of the emotion regulation questionnaire by experts was 91.25%. Media trials in small groups resulted in 83.64% while in limited groups the percentage was 81.16%. The pretest and posttest results show that the mean posttest difference is 90.31%, while the pretest results are 81.03%. This indicates that there has been an increase in students' emotional regulation abilities after using science-education based board game learning media